Le goût de l'histoire politique: les "Colloques de l'UQAM sur les leaders politiques du Québec contemporain" (1987-2002) - Corbo, Claude (Bulletin d'histoire politique, 2006)
issued: 2006-23-00
Keywords: Histoire; Université du Québec à Montréal

Des "études" médiévales à "l‘histoire" médiévale. L’essor d’une spécialité dans les universités québécoises francophones - Potter, Marc; Gingras, Yves (Revue d'histoire de l'éducation / Historical Studies in Education, 2006)
Number: 1
Keywords: Histoire; Université de Montréal; Université du Québec à Montréal

L’histoire urbaine environnementale au Québec. Un domaine de recherche en émergence - Poitras, Claire (Globe: revue internationale d’études québécoises, 2006)
Number: 1
Keywords: Histoire

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

Un historien sans histoire: Maurice Séguin et les Normes - Méchoulan, Éric (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice

Maurice Séguin et la "nouvelle histoire" - Parent, Sébastien (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice; Université de Montréal

Autour de Chénier: les Rebellions et la conscience historique canadienne et québécoise - Collin, Marc (Université Laval, 2006)
Keywords: Histoire; Rébellions

L’influence de l’historien Maurice Séguin sur l’historiographie québécoise de 1950 à 1980 - Lavallée, Josiane (Université de Montréal, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice

L’historiographie récente sur Wilfrid Laurier - Nichols, Jean-Mathieu (Université du Québec à Montréal, 2006)
Keywords: Histoire; Libéralisme; Élections

La nation et l'historicité chez Maurice Séguin - Bourque, Gilles (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice

Une lecture politologique des Normes de Maurice Séguin - Monière, Denis (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice

Pessimisme et optimisme historiques chez Maurice Séguin et Fernand Dumont - Goyette, Julien (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice

L'influence de Maurice Séguin sur l'enseignement - Allard, Michel (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Séguin; Maurice; Université de Montréal

La construction du réseau de correspondants de Lionel Groulx en milieu minoritaire, ou la solidarité nationale à l'oeuvre - Bock, Michel (Envoyer et recevoir: lettres et correspondances dans les diasporas francophones, 2006)
Keywords: Francophones; Groulx; Lionel; Histoire; Nationalisme

Le néonationalisme et la mouvance de l'historiographie québécoise au cours du dernier demi-siècle - Tousignant, Pierre (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Histoire; Historiens; Nationalisme; Séguin; Maurice; Université de Montréal

De Lionel Groulx à Maurice Séguin: mutation ou développement? - Trépanier, Pierre (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Groulx; Lionel; Histoire; Historiens; Nationalisme; Séguin; Maurice; Université de Montréal

Lionel Groulx et Maurice Séguin: dialectique de la continuité et de la rupture - Boily, Frédéric (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Groulx; Lionel; Histoire; Historiens; Nationalisme; Séguin; Maurice; Université de Montréal

Maurice Séguin et sa critique de l'optique nationaliste-fédéraliste de Lionel Groulx - Comeau, Robert (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Groulx; Lionel; Histoire; Historiens; Nationalisme; Séguin; Maurice; Université de Montréal

L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise - Comeau, Robert; Lavallée, Josiane (Septentrion, 2006)
Keywords: Brunet; Michel; Groulx; Lionel; Histoire; Historiens; Nationalisme; Séguin; Maurice; Université de Montréal

Lionel Groulx, l'École de Montréal et le destin de la nation - Bock, Michel (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Brunet; Michel; Groulx; Lionel; Histoire; Historiens; Nationalisme; Séguin; Maurice; Université de Montréal

Le fascisme de Lionel Groulx selon Gérard Bouchard - Boily, Frédéric (Bulletin d'histoire politique, 2006)
issued: 2006-24-00
Keywords: Groulx; Lionel; Idéologies

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

What Else Could We Have Done? The Montreal Jewish Community, the Canadian Jewish Congress, the Jewish Press and the Holocaust - Beer, Max (Université Concordia, 2006)
Keywords: Canadian Jewish Chronicle; Juifs

La route et ses passagers dans les romans rédigés au Québec au XIXe siècle: outils de représentation de la mobilité - Bousquet, Eveline (Université de Montréal, 2006)
Keywords: Roman

Un historien dans la Cité: Gilles Villemure (1933-2005) - Laporte, Gilles (Bulletin de l'Association des professeures et des professeurs d'histoire des collèges du Québec, 2006)
issued: 2006-24-00
Keywords: Historiens

Une histoire sociale du curling au Québec, de 1807 à 1980 - Richard, Pierre (Université du Québec à Trois-Rivières, 2006)
Keywords: Clubs; Curling; Femmes; Francophones; Montreal Curling Club

Le ciné-club étudiant au Québec, un véhicule d'ouverture à la modernité culturelle, 1949-1970 - Ménard, Olivier (Université de Sherbrooke, 2006)
Keywords: Cinéma; Jeunesse étudiante catholique; Office national du film; Étudiants

De colombine à Julien Saint-Michel: le féminisme chez Éva Circé-Côté (1900-1921) - Létourneau, Émilie (Université de Sherbrooke, 2006)
Keywords: Circé-Côté; Éva; Féminisme; Journalistes

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Keywords: Chanson; Musique

La crise de Saint-Léonard dans la presse montréalaise, 1968-1969 - Chikli, Christophe (Université de Sherbrooke, 2006)
Keywords: Devoir (Le); Italiens; Langue; Montreal Gazette; Montreal Star; Presse (La); Saint-Léonard (crise de)

Pierre-Joseph-Olivier Chauveau: portrait en trois temps - Gallichan, Gilles (Histoire Québec, 2006)
Number: 2
Keywords: Chauveau; Pierre-Joseph-Olivier; Députés; Shérifs; Écrivains

Marie Victorin, La Flore Laurentienne, 1935 - Gingras, Yves (Monuments intellectuels québécois du XXe siècle: grands livres d'érudition, de science et de sagesse, 2006)
Keywords: Botanique; Flore; Marie-Victorin; Frère

Les disciples de Maurice Séguin: un regard sur deux générations d'historiens - Lavallée, Josiane (L'historien Maurice Séguin. Théoricien de l'indépendance et penseur de la modernité québécoise, 2006)
Keywords: Historiens; Séguin; Maurice; Université de Montréal

Le frère Marie-Victorin, l’âme du Jardin botanique - Gingras, Yves (Quatre-temps, 2006)
Number: 2-3
Keywords: Botanique; Jardin botanique; Marie-Victorin; Frère

Pierre Le Moyne d’Iberville (1706-2006): trois siècles à hue et à dia - Andrès, Bernard (Les Cahiers des dix, 2006)
Number: 60
Keywords: Le Moyne d'Iberville et d'Ardillières; Pierre

Patrimoine urbain et urbanisme à Montréal: l'expérience du début des années 2000 - Garcia, Sylvain (Université de Montréal, 2006)
Keywords: Patrimoine

Est-on quitte envers le passé? Borduas, Vadeboncoeur et le dénouement de « notre maître, le passé » - Lamonde, Yvan (Les Cahiers des dix, 2006)
Number: 60
Keywords: Borduas; Paul-Émile; Idéologies; Peinture

Le spectacle de nos contradictions: trusts de production et troupes populaires, puritanismes orthodoxes et folies fin de siècle. Le théâtre au Québec, 1880-1899 (première partie) - Bourassa, André (Bulletin d'histoire politique, 2006)
issued: 2006-23-00
Keywords: Théâtre

Nouveau regard sur l'antisémitisme: enquête sur la position de cinq quotidiens canadiens-français au sujet de la question juive en Allemagne (1935-1939) - Côté, Olivier (Bulletin d'histoire politique, 2006)
issued: 2006-23-00
Keywords: Juifs

Sir William Logan and Sir J.W. Dawson: Victorian Geology as Scottish Science in a New World Environment - Zeller, Suzanne (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Dawson; William; Géologie; Logan; William Edmond; Écossais

The Curious Tale of the Scots and the Fur Trade: An Historiographical Account - Bumsted, J. M. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Fourrure; Écossais

La Pointe-aux-Trembles: aire de loisirs des Montréalais - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2006)
Keywords: Pointe-aux-Trembles; Quartiers

Retrouver la ville à la campagne: la villégiature à Montréal au tournant du XXe siècle - Aubin-Des-Roches, Caroline (Urban History Review / Revue d'histoire urbaine, 2006)
Number: 2

Les revues intellectuelles entre empêchement et émancipation, 1950-1968 - Carel, Ivan (Université du Québec à Montréal, 2006)
Keywords: Action nationale (L'); Cité Libre; Parti Pris

The Montréal First Nine: a Study of English Language Newspaper Coverage of Baseball in Nineteenth Century Montréal - Braganza, Paul Michael Henry (Université Concordia, 2006)
Keywords: Baseball

Par-delà la ténacité et l’abnégation. La presse musicale au Québec 1890-1959 - Tremblay, Jean-Philippe (Université du Québec à Montréal, 2006)
Keywords: Musique

Fréquentations et mariage, les représentations de jeunes québécoises à travers l'étude d'un courrier du coeur (1958-1968) - Sénéchal, Johanne (Université Laval, 2006)
Keywords: Bertrand; Janette; Femmes; Mariage

La réaction de l'épiscopat québécois à l'industrialisation de la presse, 1884-1914 - Guérin, Andréanne (Université Laval, 2006)
Keywords: Édition; Évêques

L’idéal maternel: discours, représentation et célébration des mères québécoises à l’occasion de la fête des mères, 1940-1980 - Marando, Nancy (Université de Montréal, 2006)
Keywords: Enfants; Famille; Femmes; Montreal Star; Presse (La)

Les règles du jeu de la séduction dans les manuels de savoir-vivre québécois (1863-1917): investir le monde du sentiment et de l’intimité masculine - Roy, Sonya (Université de Montréal, 2006)
Keywords: Bourgeoisie; Mariage

The Architecture and Painting Collection of the Mount Royal Club Montreal 1899-1920 - Banham, Kathryn J. (Université Concordia, 2006)
Keywords: Clubs; Mount Royal Club; Peinture

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

En marge, les circuits des livres d'artistes à Montréal après 1980 - Morin, Marie-Josée (Université de Montréal, 2006)

A Metropolitan Line: Robert LaPalme (1908-1997): Caricature and Power in the Age of Duplessis (1936-1959) - Hardy, Dominic Llywelyn (Université Concordia, 2006)
Keywords: Caricature